Do Linear Transport Infrastructures provide a potential corridor for urban biodiversity? Case study in Greater Paris, France - Laura Clevenot (Unité Mixte de Recherche 8504 Géographie-cités, 2017)
Recent studies have emphasised the increasing impact, both negative and positive, of Linear Transport Infrastructures (LTIs) on biodiversity. A significant body of scientific and technical knowledge is more and more available to help guide restoration practices concerning especially urban areas. This study explores a comprehensive approach to estimating restoration potential along the LTI edges in the Greater Paris region (in France) in terms of potential biodiversity. Our work consists in inventorying and analysing the Potential Biodiversity Index, PBI, on sites along two LTIs crossing a forest in the northern part of this district. The study concerns a Natura 2000 area, La Poudrerie Park. A total of 84 surveys were carried out corresponding to the 33 hectares surveyed. We studied sites along the LTIs. For this purpose, we chose 84 sites in the traffic corridors. Biodiversity parameter evaluations were performed for each site. These parameters are related to functional traits that make it possible to determine the Potential Biodiversity Index (PBI). These site assessments by PBI may reveal the positive impact of the LTI edges in developing biodiversity. We may establish that there is a positive impact of LTIs edges for ecological restoration and revegetation in an urban context.